Pathogenic and non-pathogenic Escherichia coli colonization and host inflammatory response in a defined microbiota mouse model - Zachary R. Stromberg; Angelica Van Goor; Graham A. J. Redweik; Meghan J. Wymore Brand; Michael J. Wannemuehler; Melha Mellata (The Company of Biologists, 2018)
Most Escherichia coli strains in the human intestine are harmless. However, enterohemorrhagic E. coli (EHEC) is a foodborne pathogen that causes intestinal disease in humans. Conventionally reared (CONV) mice are inconsistent models for human infections with EHEC because they are often resistant to E. coli colonization, in part due to their gastrointestinal (GI) microbiota. Although antibiotic manipulation of the mouse microbiota has been a common means to overcome colonization resistance, these models have limitations. Currently, there are no licensed treatments for clinical EHEC infections and, thus, new tools to study EHEC colonization need to be developed. Here, we used a defined microbiota mouse model, consisting of the altered Schaedler flora (ASF), to characterize intestinal colonization and compare host responses following colonization with EHEC strain 278F2 or non-pathogenic E. coli strain MG1655. Significantly higher (P<0.05) levels of both strains were found in feces and cecal and colonic contents of C3H/HeN ASF compared to C3H/HeN CONV mice. GI inflammation was significantly elevated (P<0.05) in the cecum of EHEC 278F2-colonized compared to E. coli MG1655-colonized C3H/HeN ASF mice. In addition, EHEC 278F2 differentially modulated inflammatory-associated genes in colonic tissue of C3H/HeN ASF mice compared to E. coli MG1655-colonized mice. This approach allowed for prolonged colonization of the murine GI tract by pathogenic and non-pathogenic E. coli strains, and for evaluation of host inflammatory processes. Overall, this system can be used as a powerful tool for future studies to assess therapeutics, microbe-microbe interactions, and strategies for preventing EHEC infections.